ANALYSIS OF THE EFFECT OF CONTRACT CHANGE ORDER FACTORS ON THE PERFORMANCE OF ROAD FACILITY PROJECTS - Dhona Lailatul Qomariah; Budi Susetyo (LPPM Universitas Negeri Jakarta, 2024)
Road facilities are part of the national transportation system according to Article 25 in Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation. Road facilities in the form of sidewalks and crossings are crossings for pedestrians. The arrangement of sidewalks by the DKI Jakarta Provincial Government is to improve urban infrastructure, where the percentage of sidewalk arrangements by 2022 will reach 5.58% of the length of roads in Jakarta. This research aims to determine the influence of factors Contract Change Order (CCO) on cost performance and implementation time for sidewalk arrangement activities, using structural equation modeling techniques-partial least squares (SEM-PLS). This research focuses on identifying the main CCO factors that directly influence cost performance, and indirectly influence implementation time performance through cost performance on road facility projects. There are 3 (three) types of research variables used; The independent variables consist of scope of work, planning, policy changes, specification changes, and coordination of related parties, the dependent variable is cost performance and the intervening variable is cost performance as a mediating variable of the influence of the CCO factor on time performance. The results showed that the coordination of related parties had a direct and significant positive impact on cost performance by 59%, and an indirect and significant impact on time performance through cost performance as a mediating variable by 37.7%.